PENGARUH BENTONIT PER ORAL TERHADAP PENURUNAN KADAR GLUKOSA DARAH TIKUS MODEL DIABETES MELITUS YANG DIINDUKSI ALOKSAN MONOHIDRAT - Galuh Alviana; Hendro Sudjono Yuwono; Nova Sylviana (PAIFORI, 2020)
In Indonesia, it is estimated that there would be increasing in number of diabetes mellitus patients become 12 million cases in 2030. The expensive cost of conventional medications motivates people to find alternative medication. Bentonite is a natural clay which is a good absorbent and frequently called as healing clay for its potency in body detoxification. This study is an experimental research to prove bentonite which is a good absorbent and adsorbent in decreasing blood glucose concentration in diabetes mellitus. Subject of this research is 20 female Wistar rats which weigh 150–250 g. These subjects were divided into two groups: control group and bentonite group. Diabetes is induced by alloxan monohydrate 150mg/kg intraperitoneally, causing β cell necrosis in pancreas. Result of independent t-test showed that bentonite could significantly lower blood glucose levels with average value of 131.30 mg/dL (p=0.010). This concludes that bentonite canreduce blood glucose level in diabetic-induced rats.